Euroscepticism, Europhobia and Eurocriticism - Rodríguez-Aguilera de Prat, Cesáreo (2013)
Euroscepticism has become a generic catch-all term that is not always useful to capture the nuances of the different types of political opposition to the current process of European integration. This research analyses the electoral manifestos and programmes presented to the European Parliamentary elections in 2009 by twenty-two parties. In this regard, it is clear that the radical right parties usually have Europhobic impulses – their rejection being not only of methods, but also of principals. In contrast, the radical left parties are, in theory, favourable to European integration, but dispute the direction imposed by the EU authorities.